Perilaku konsumtif mahasiswa melalui aplikasi TikTok Shop ditinjau dari Perspektif Jean Baudrillard - Hadisaputra Hadisaputra; Andi Asywid Nur; Asika Zahra; Melisa Febrianti Sofyan (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2025)
This research aims to reveal patterns of consumer behavior and identify the impacts of such behavior among students at Unismuh Makassar. Using qualitative methods and a case study approach, the research explores the dynamics behind students' purchasing decisions through data collection techniques such as observation, interviews, and document analysis. The findings of this study indicate that Unismuh Makassar students exhibit high levels of consumerism, driven by a desire to appear fashionable and take advantage of various discounts offered during events like the TikTok Shopping 12.12 Mega Sale. Additionally, their behavior is influenced by marketing strategies involving public figures or their favorite celebrities. This consumerism is not only driven by the need to conform to social norms and enhance self-image but also by the influence of social media and the phenomenon of hyperreality, as explained in Jean Baudrillard's theory of simulacra and simulation. The impact of this consumer behavior is twofold: on one hand, there is an increase in self-confidence among the students; on the other hand, this behavior often leads to negative effects such as overspending, which can disrupt students' financial stability and reduce their ability to save and invest for the future.